Analysis of the Need for Canva-Based Electronic Modules to Improve Vocational Learning Outcomes - Ade Holisoh; Henny Setiani; Hendi Firdaus; Lukman Nulhakim; Yayat Ruhiat (Postgraduate, University of Mataram, 2023)
The goal of education is not just to increase one's head knowledge, but also one's skill set, outlook, and frame of mind. Learning results are affected by the quantity and quality of reading resources available in schools.